Anatomical Considerations of Embryology and Development of the Musculoskeletal System: Basic Notions for Musculoskeletal Radiologists - Aparisi Gómez, Maria Pilar; Watkin, Sheryl; Perry, David; Simoni, Paolo; Trisolino, Giovanni; Bazzocchi, Alberto (Seminars in Musculoskeletal Radiology, 2021)
The musculoskeletal (MSK) system begins to form in the third week of intrauterine development. Multiple genes are involved in the complex different processes to form the skeleton, muscles and joints. The embryonic period, from the third to the eighth week of development, is critical for normal development and therefore the time when most structural defects are induced. Many of these defects have a genetic origin, but environmental factors may also play a very important role. This review summarizes the embryology of the different components of the MSK system and their configuration as an organ-system, analyzes the clinical implications resulting from failures in the process of organogenesis, and describes the first approach to diagnosis of skeletal abnormalities using prenatal ultrasound.
Keywords: musculoskeletal; ultrasound; dysostosis; embryology; congenital